Analyze The Mediating Role of Organizational Silence in the Relationship Between Abusive Supervision and Workplace Deviance Behaviors: Applying on Nursing Staff in Public Hospitals at Beni-Suef Governorate - Abdel Kader, Khaled Abdel Kader Mohamed (The Arab Journal of Administration, 2024)
The research aimed to test the direct effect of abusive supervision as an independent variable on both organizational silence and Workplace Deviance Behaviors as dependent variables, as well as the direct effect of organizational silence as an independent variable on Workplace Deviance Behaviors as a dependent variable, as well as testing the mediating role of organizational silence on the relationship between abusive supervision. and Workplace Deviance Behaviors. To achieve this goal, the researcher selected a sample of (298) individuals working in the nursing staff in Egyptian government hospitals in Beni Suef Governorate. Using the structural equations path analysis method, the research found that there is a direct positive effect of abusive supervision on both organizational silence and Workplace Deviance Behaviors. It also found that there is a direct positive effect of organizational silence on Workplace Deviance Behaviors. The research also found a significant partial mediating role for organizational silence in the relationship between abusive supervision and Workplace Deviance Behaviors. Abusive supervision directly affects Workplace Deviance Behaviors, but when organizational silence was introduced as a mediating variable, the total effect of abusive supervision on Workplace Deviance Behaviors increased.